Contemporary Africa : challenges and opportunities - Toyin Falola; Falola, Toyin; Mbah, Emmanuel M.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
60 years after independence, African nations still find it difficult to face a number of challenges, from establishing meaningful democratic institutions to establish social structures centered on the advancement of gender equality. This volume approaches these contemporary African challenges while combating a reflexive and facile Afro-Pessimism.
Keywords: Science; Science; Science, general